The negative impact of the COVID‐19 pandemic on UK haematology registrars' well‐being and training: Results of a UK nationwide survey. Issue 4 (26th August 2021) - Altohami, Mohammed OA; Langridge, Alexander; Shareef, Enas MK; Nicolson, Phillip LR
Abstract: The COVID‐19 pandemic has disturbed medical training. Haematology registrars were surveyed using SurveyMonkey. Eighty‐nine out of 269 (24.9%) responded. Reported stressors included concerns about transmitting the infection, disruption of leave, inferior patient outcomes, survivors' guilt and interruption of career progression. Only 31.2% felt ready to progress to the next training stage. Reported causes of lack of training were disruption of clinics and training days and utilisation of telephone consultations. Several stressors negatively impacted haematology registrars' well‐being, training and progression. More emphasis on psychological support, outpatient clinic work and e‐learning is needed.